A MATHEMATICAL MODELING TO DETERMINE SUPPLIER CONTRACTS IN TRANSPORTATION PLANNING - FRANSISKA HERNINA PUSPITASARI (Universitas Mercu Buana, 2019)
Transportation plays some important roles in supply chain management. It contributes significantly towards a business performance. Therefore, a company needs to plan its transportation system. A good transportation planning is able to lead in either efficiency or responsiveness. This paper addresses to build a mathematical model of determination of supplier contracts in a transportation problem. In this case, a company already selected a supplier partnership or, in other words, third-party logistics (3PLs) who provides trucks to be rented. The 3PLs also offers three options of contracts to the company, and the company should sign which contracts that can minimize rental costs and meet the company’s demands. This model is a linear-programming model. Using a numerical example, the problem is solved with LINGO.